On some aspects of the legal regulation of theproduction of documents to the court of the «Astana» international financial center (Journal of actual problems of jurisprudence, 2023)
The activity of the Court of the «Astana» International Financial Center is under the close attention of researchers in the field of substantive law. Meanwhile, some aspects of the legal regulation of administration of justice in the Court of the «Astana» International Financial Center remain without due attention from the scientific community. The author has made an attempt to study the procedural order of production of documents by the Parties to each other at the stage of pre-trial preparation for the proceedings in the Court of the «Astana» International Financial Center. The article is devoted to the legal regulation of the process of production of documents in the civil process of the Court of the "Astana" International Financial Center. The author notes the exclusivity of this institution and pays attention to the correlation of production of documents and disclosure of evidence. The article made an attempt to determine the purpose and objectives of the phenomenon under study, to designate subjects and objects of the production of documents at the stage of pre-trial preparation for consideration of the case. Comparative-legal analysis of norms of the Rules of the Court of the «Astana» International Financial Center with acting norms of Civil Procedure Code of the Republic of Kazakhstan allows to come to a conclusion about difference of procedure of documents' production in the Court of the «Astana» International Financial Center and presentation of evidence in the courts of general jurisdiction of Kazakhstan. The article will be interesting for practicing lawyers, in order to fill the gaps of knowledge regarding the procedure of production of documents, for more successful representation of clients' interests in the Court of the «Astana» International Financial Center. Scientific relevance of the study is determined by the novelty of the phenomenon of production (disclosure) of documents for domestic science, requiring a closer and more detailed study in order to possible further borrowing in the national legislation.Keywords: civil procedure, evidence, Court of «Astana» International Financial Center, disclosure of evidence, evidence, common law.